2017
DOI: 10.5897/ajar2016.12095
|View full text |Cite
|
Sign up to set email alerts
|

The sowing density on oat productivity indicators

Abstract: The sowing density adjustment in oatcan maximize the productivity expression.The aim of this study is to define the behavior of productivity expression of biomass, grains, straw andharvest indexthrough increasing sowing density in the main biotype cultivated in Southern Brazil. It proposesthe possibility of indicating higher sowing density to the productivity maximization of biomass and grains.With the densityadjusted to the grain productivity to simulate the reflexes on the biological and straw productivity a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Data obtained in the field regarding the different seeding densities were subjected to second-order polynomial regression analysis, commonly used in the optimization and simulation of factors with quantitative training levels (Romitti et al, 2017). After meeting the assumptions of homogeneity and normality by Bartlett's test, analysis of variance of regression was conducted to detect main and interaction effects.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data obtained in the field regarding the different seeding densities were subjected to second-order polynomial regression analysis, commonly used in the optimization and simulation of factors with quantitative training levels (Romitti et al, 2017). After meeting the assumptions of homogeneity and normality by Bartlett's test, analysis of variance of regression was conducted to detect main and interaction effects.…”
Section: Methodsmentioning
confidence: 99%
“…Studies aiming at simulation and optimization with the oat crop through AI via artificial neural networks and genetic algorithms are inexistent in the Brazilian research, although they can contribute to important processes related to the management of the species. Since the expression of oat grain yield depends on seeding density (Silva et al, 2012;Romitti et al, 2017), using different densities in the alteration of grain yield may serve as basis for training the network and validate the use of AI for simulation and optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Oats are considered a multi-purpose cereal, used for soil cover due to the high volume of straw it produces (Godoy et al, 2016;Queiroz et al, 2017), and for animal feed in the form of pasture, hay, silage, and as an ingredient of feed concentrates (Romitti et al, 2017;Dornelles et al, 2018). For human consumption, it is possible to produce numerous products, with nutritional and functional qualities superior to those of other cereals (Sancho and Pastore, 2016;Mantai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…4.2). Other investigators have also found a quadratic response or no response in grain yield Ciha, 1983;Peltonen-Sainio and Jarvinen, 1994;Marcos et al, 2017) and are different than those in which yields increased linearly Peltonen-Sainio and Jarvinen, 1994;Benaragama and Shirtliffe, 2013).…”
Section: Grain Yieldmentioning
confidence: 78%